Welcome to the TheoLab - Karcher, Stefan (TheoLab Blog, 2020)
Theologians have to read - a lot! The fact that theological disciplines rely on multiple fields of the textual sciences makes for a larger number of sources and a more diverse amount of literature compared to other fields in the humanities. If you want to understand the texts of the Bible, you need to be conversant in philological and historical methods ...